Comparing the mixed model and the fixed effects model: Do the advantages justify the costs? - Duchateau, L. (International Biometric Society, 1997)
Mixed models have important advantages as compared to fixed effects models. Complex data structures can be described in a natural way in mixed models. The analysis of unbalanced data is a straightforward extension of the analysis of balanced data in the mixed model framework. Furthermore, the appropriate inference space can be chosen in the mixed model. We further try to answer the question whether the advantages of the mixed model outweigh the cost one has to pay to use this methodology in the context of developing countries.